Strategies for Homeroom Teachers in Fulfilling Their Dual Roles as Teachers and Surrogate Parents in Fostering Students’ Moral Character at MIN Maros - Rusniati; Mumtahanah; Muhammad Warif; Mujahidah (Yayasan pendidikan dzurriyatul Quran, 2026)
The homeroom teacher plays a crucial role in character formation, not only as an academic educator but also as a second parent who guides students' moral development. However, research specifically examining homeroom teacher strategies in fulfilling this dual role in Islamic elementary schools remains limited. This study aims to describe the forms of the homeroom teacher's dual role, analyze the strategies used in students' moral development, and identify the inhibiting factors encountered in its implementation. This study employed a qualitative approach with a case study design, conducted at MIN Maros. Data were collected through in-depth interviews, participatory observation, and documentation. Research informants consisted of the Class III A homeroom teacher as the key informant, the school principal, students, and parents as supporting informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with validity tested through source triangulation, technique triangulation, and time triangulation. The results show that: (1) the homeroom teacher performed the dual role as teacher and second parent through academic guidance, emotional support, personal attention, and motivation; (2) the moral development strategies applied included exemplary conduct (uswatun hasanah), religious habit formation, personal advice, educational discipline, and positive behavior appreciation; and (3) inhibiting factors included student character diversity, lack of parental support, gadget influence, and the homeroom teacher's administrative burden. This study concludes that the success of students' moral development is supported by the homeroom teacher's consistency in integrating pedagogical and nurturing functions.